(untitled) (Texas Journal of Philology, Culture and History, 2024)
The significance of fostering a communicative culture among students studying English as a foreign language (EFL) is one of the actual concerns in current language teaching processes. To succeed in utilizing English in everyday situations, language learners must possess effective communication skills. This article explores methods and approaches that educators can use to encourage communication in EFL classes, which can eventually improve students’ confidence and language skills.